Travel Hopefully: The Obvious and not so Obvious Dividends from Professional Investments. Issue 1 (2nd January 2019) - Dustin, Daniel L.; Wright, Brett; Harper, Jack; Lamke, Gene; Murphy, James; McDonald, Cary
Abstract: To travel hopefully is to have faith that an investment today will pay dividends tomorrow. In this article, the authors discuss several different kinds of professional investments that have paid off for them throughout their academic careers. Some of these dividends are obvious. They can be measured in dollars and cents earned as a result of sustained professional involvement. Other dividends are less obvious. They can be measured in a wealth of relationships and experiences that contribute to a full and satisfying life. While acknowledging the importance of financial dividends, especially early in one's career, the authors emphasize the importance of social/relational dividends that enrich later life.